Vicinal Dichlorination of o-Vinylbiphenyls and the Synthesis of 9-(Arylmethyl)fluorenes via Tandem Friedel–Crafts Alkylations - Zhao, Zhensheng; Jameel, Islam; Murphy, Graham K. (Synthesis, 2019)
Reacting ortho-vinylbiphenyls with (dichloroiodo)benzene (PhICl2) gives vicinal dichlorides, rapidly, and in excellent yield at room temperature. Treating the vic-dichlorides with 50 mol% AlCl3 in the presence of arene nucleophiles results in sequential intramolecular and intermolecular Friedel–Crafts alkylations to generate 9-(arylmethyl)fluorene derivatives. The dichlorination and alkylation reactions are operationally simple and tolerant of a variety of functional groups and substitution patterns, and give the products in moderate to excellent yield.
Keywords: fluorene; 1-aryl-1,2-dichloroethane; chlorination; hypervalent iodine; Friedel–Crafts